The impact of chronic urticaria on the quality of life in Indian patients - A V Pherwani; G Bansode; S Gadhia (Wolters Kluwer Medknow Publications, 2012)
Backgound : Besides the relief of symptoms, the main purpose of any treatment must be to ensure a better quality of life (QOL). Mere recording of symptoms reveals their severity and frequency, but gives scant information on its effect on QOL. Aim: The study was designed to assess QOL in Indian patients with chronic urticaia (CU). Subjects and Methods: We used the validated CU-QOL by Bairadani et al., consisting of five domains and each domain consisting of several items. Each item was scored from 1 to 5 (score 5 = most affected, score 1 = not affected). Criteria for Inclusion: Patients having symptoms of rash and pruritis on most of the days for at least 6 weeks were enrolled. Criteria for Exclusion: If the individuals had CU secondary to any other disease, they were excluded. Results: We enrolled 48 patients. The means of the domains, the items, and the frequency of occurrence of an item were tabulated. The highest mean scores were in the domains of symptoms, followed by sleep disturbances, life activities, looks, and limits. The highest mean scores for the items were for pruritis and wheals followed by sleep disturbances, mood changes, nervousness, embarrassment, fatigue, loss of concentration, reduced work, and social relationships. We also observed a significant relationship among individual items. It is possible that they may have an additive effect. Conclusions: Even though CU significantly affected many items, patients were rarely aware of them. There was a significant inter-item correlation, suggesting that items might be aggravating each other. It is important to address the issues regarding QOL along with symptoms for better management of CU.